2015
DOI: 10.5539/jsd.v8n2p196
|View full text |Cite
|
Sign up to set email alerts
|

Economic Growth and Biodiversity: An Overview Conservation Policies in Africa

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 62 publications
0
8
0
Order By: Relevance
“… 19 21 Clarifying the implications of a green environment for population mental health is important because this can contribute key evidence to the ongoing sustainable development debate around how to balance biodiversity conservation and economic growth for sustainable development within a resilient environment. 22 …”
Section: Introductionmentioning
confidence: 99%
“… 19 21 Clarifying the implications of a green environment for population mental health is important because this can contribute key evidence to the ongoing sustainable development debate around how to balance biodiversity conservation and economic growth for sustainable development within a resilient environment. 22 …”
Section: Introductionmentioning
confidence: 99%
“…found that, open access nature of some resources and externality of market-oriented activities are the main causes of extinction and biodiversity losses (Berk;1979;Pearce and Turner, 1990;Pearce, 2007;Iritié, 2015). Bishop (1993) also pointed that, the extinction of living organisms such as fish is of economic concern because it may affect the sustainability of the resources and lead to economic losses imposed on future generations.…”
Section: Conceptual Frameworkmentioning
confidence: 99%
“…This already occurs in some jurisidctions, such as France, where the development of biodiversity offsets requires negotiation with relevant stakeholders to ensure their interests are considered (Guillet & Semal, 2018). Stakeholder input and/or community consultation is needed to ensure that issues around conservation activities are resolved (Iritie, 2015;Rohr et al, 2018;Taherzadeh & Howley, 2016). Milestones also may need to include aspect of disturbance, as some species will only recruit to disturbed or structurally modified ecosystems (Tierney et al, 2017).…”
Section: Monitoring and Measures Of Offset Successmentioning
confidence: 99%
“…anthropogenic pressures, such as fishing), or areas where risk is too high/costs are too great for compensation. While the use of biodiversity offsets markets can be used to fill gaps in conservation priorities (Iritie, 2015), this can also be achieved by ensuring that offsets are linked to planning frameworks. Ultimately, if used in combination, greater cost and risk efficiencies may be achieved.…”
Section: Incorporation Of Biodiversity Offsets In Planning Frameworkmentioning
confidence: 99%